A multifaceted approach to RSV vaccination - Jorge C. G. Blanco; Marina S. Boukhvalova; Trudy G. Morrison; Stefanie N. Vogel (Taylor & Francis Group, 2018)
Respiratory Syncytial Virus (RSV) is the leading cause of pneumonia and bronchiolitis in infants, resulting in significant morbidity and mortality worldwide. In addition, RSV infections occur throughout different ages, thus, maintaining the virus in circulation, and increasing health risk to more susceptible populations such as infants, the elderly, and the immunocompromised. To date, there is no vaccine approved to prevent RSV infection or minimize symptoms of infection. Current clinical trials for vaccines against RSV are being carried out in four very different populations. There are vaccines that target two different pediatric populations, infants 2 to 6 month of age and seropositive children over 6 months of age, as well as women (non-pregnant or pregnant in their third trimester). There are vaccines that target adult and elderly populations. In this review, we will present and discuss RSV vaccine candidates currently in clinical trials. We will describe the preclinical studies instrumental for their advancement, with the goal of introducing new preclinical models that may more accurately predict the outcome of clinical vaccine studies.